Acute Intermittent Porphyria: Current Perspectives And Case Presentation - Spiritos Z; Salvador S; Mosquera D; Wilder J (Dove Medical Press, 2019)
Zachary Spiritos,1 Shakirat Salvador,2 Diana Mosquera,3 Julius Wilder1,4 1Department of Medicine, Division of Gastroenterology, Duke University School of Medicine, Durham, NC, USA; 2Department of Medicine, Division of Gastroenterology, Vanderbilt University Medical Center, Nashville, TN, USA; 3Department of Medicine, Duke University School of Medicine, Durham, NC, USA; 4Department of Medicine, Duke Clinical Research Institute, Durham, NC, USACorrespondence: Julius WilderDepartment of Medicine, Division of Gastroenterology, Duke University School of Medicine, Durham, NC, USATel +1 919 668 3063Fax +1 919 668 7164Email julius.wilder@duke.eduAbstract: Acute intermittent porphyria (AIP) is an autosomal dominant metabolic disorder characterized by a deficiency in heme biosynthesis. Heme biosynthesis occurs throughout the body, but it is most prominent in the erythroblastic system and liver. AIP is a hepatic porphyria whereby the liver is the source of toxic heme metabolites. Clinical manifestations of AIP result from a genetic mutation that leads to partial function of porphobiliogen deaminase (PBGD). This causes an accumulation of upstream, neurotoxic metabolites. Symptoms include but are not limited to peripheral neuropathies, autonomic neuropathies and psychiatric manifestations. AIP can be life threatening and clinical signs and symptoms are often heterogeneous and non-specific. Therefore, it is important to be able to recognize these patients to make a prudent diagnosis and offer appropriate therapy. Here, we review the epidemiology, pathophysiology, clinical presentation, diagnosis, and management of AIP including the role of liver transplantation.Keywords: acute porphyria, acute intermittent porphyria, hepatic porphyria